KUALITAS PELAYANAN PEMBUATAN AKTA JUAL BELI TANAH DI KECAMATAN PINELENG KABUPATEN MINAHASA - KAWULUSAN, ALFRIT; RURU, JOORIE; LONDA, VERY (JURNAL ADMINISTRASI PUBLIK, 2020)
The purpose of this study was to determine the Quality of Service for Making Land Purchase Deed in theDistrict of Pineleng, Minahasa Regency. This research uses qualitative research methods. There are 8informants in this study consisting of sub-district heads (1 person), sub-district secretaries (1 person), subdistrictstaff who handle AJB (1 person), and the community (5 people). Based on the results of researchthat has been done by the author, In general the Service Quality of Making Land Purchase Deed can beseen from 3 (three) dimensions of service quality, namely: (1) Reliability (reliability) here the reliability ofemployees in providing services that are fast, precise, easy and smoothly becomes an evaluation conditionfor the people being served. In terms of speed, the accuracy of employees in the Pineleng District Officewhen making arrangements or services can be said to be quite good. However, there are still people who,when making arrangements, still lack understanding of the completeness of the file, which is the obstaclehere, namely the lack of providing information about AJB management procedures to the public. (2)Responsiveness (responsiveness), the service procedure for making Land Purchase Deed in PinelengDistrict in this case regarding the responsiveness of its employees when performing services to thecommunity can be said to be good and for the level of absorption, the understanding of all complaints andunderstandings to the community is also quite good . (3) Empathy (empathy), shows the ability to understandthe people who are served with attention, seriousness, sympathetic, and understanding. According to all theinformants' answers, the empathy attitude from the employees was good enough, but there were still peoplewho could not complete the management process. The problem is the lack of employee openness to thecommunity. And also still found special treatment to other communities.Keywords: Quality, Service, Land Purchase Deed